ANALISIS PENERAPAN PAJAK PERTAMBAHAN NILAI (PPN) PADA PT. ARMADA SAMUDERA RAYA - EY. Suharyono, Dari Layani Gea, Titin Ruliana, (EKONOMIA, 2020)
Taxes are one of the sources of state revenues that have huge benefits and greatly influence the welfare of the people. To maximize state revenues, one way that government agencies must implement is by issuing laws governing taxation.The purpose of this study is to find out the application of Value Added Tax (PPN) at PT. Samudera Raya Fleet based on the VAT Act No. 42 of 2009.The analytical tool used in this study is the Value Added Tax Law Number 42 of 2009 concerning the Third Amendment to Law Number 8 of 1983 concerning Value Added Tax on Goods and Services and Sales Tax on Luxury Goods. Data obtained by using documentation and observation techniques.The research results obtained from the details of freight bills and VAT tax invoices in 2018 found that PT. Armada Samudera Raya lacks deposits of tax payable to the State treasury of Rp. 344,152,744.00 this is because the company has not collected Value Added Tax (PPN) for customers from January - November 2018.The conclusion of this study is that the application of Value Added Tax (PPN) at PT. The Samudera Raya Fleet is not in accordance with the PPN Law Number 42 of 2009